THE 2004 OLYMPIC EDUCATION PROGRAMME IN GREECE AT PRIMARY AND SECONDARY SCHOOLS (Fiep Bulletin - online, 2012)
Greece hosting of the 2004 Olympic Games has brought about significant changes in the country in relation the construction of new sport facilities, major infrastructure projects, short-term and long-term economic development and the introduction of remarkable security measures. Among the most important changes is the establishment of a special Olympic Education Programme (OEP) aimed at pupils in primary, lower and higher secondary school. The Olympic Education Programme is an educational process, which seeks to educate young pupils about Olympic values, taking into account aspects of modern culture. It includes series measures, which promote and highlight the educational and instructive value of the Olympic Games. The whole programme is implemented by physical education teachers in collaboration with the Ministry of Education and Religious Affairs and the Organizing Committee for the Olympic Games – Athens 2004.
Keywords: Olympic Games; Education programme; Greece